The human/animal in contemporary South African photography. Issue 1 (2nd January 2016) - Halliday, Amy
Abstract : By looking at work by two contemporary South African photographers, this article examines some of the ways in which notions of 'the animal' intersect with human subjectivity and representation. Georgio Agamben's formulation of the Western 'anthropological machine', which works to shape human 'otherness' through recourse to the animal, provides the theoretical framework for examining Pieter Hugo's 'The Hyena and Other Men'. Invoking ideas of the 'wild' in structuring perceptions of socially marginalized groups, Hugo's ambivalent portraits have been accused of exoticising, and eroticising, black masculinity, but, read through Donna Haraway's conceptualization of companion species, may open up new readings of human/animal relationality. The 'tame' is no less contested: Daniel Naudé's 'Animal Farm' focuses on particular livestock breeds, demonstrating that domesticated animals can become a site of anxiety around human 'pedigree' too.